Pain and pain management in children and adolescents receiving hospital care: a cross-sectional study from Sweden - Viveka Andersson; Stefan Bergman; Ingela Henoch; Hanna Simonsson; Karin Ahlberg (BMC, 2022)
Abstract Background Pain is a common symptom in children receiving hospital care. Adequate pain management in paediatric patients is of the utmost importance. Few studies have investigated children's own experiences of pain during hospitalization. Aim To describe the prevalence of pain, self-reported pain intensity at rest and during movement, pain management and compliance with pain treatment guidelines in children and adolescents receiving hospital care. Furthermore, to examine self-reported statements about pain relief and how often staff asked about pain. Methods A quantitative, cross-sectional study with descriptive statistics as the data analysis method was conducted at a county hospital in western Sweden. Sixty-nine children/adolescents aged 6-18 years who had experienced pain during their hospital stay were included. A structured, verbally administered questionnaire was used to obtain pain reports. The participants were also asked what they considered alleviated pain and how often they told staff about pain. Patient demographics, prescribed analgesics and documentation of pain rating were obtained from medical records. Results Fifty children/adolescents (72%) experienced moderate to severe pain in the previous 24 hours. At the time of the interview 36% reported moderate to severe pain at rest and 58% during movement. Seven participants (10%) reported severe pain both at rest and during movement. About one-third were on a regular multimodal analgesic regimen and 28% had used a validated pain rating scale. Thirty children/adolescents (43%) reported that they had experienced procedural pain in addition to their underlying pain condition. Most of the children/adolescents (74%) reported that analgesics provided pain relief. Forty (58%) stated that various non-pharmacological methods were helpful. Conclusions Despite evidence-based guidelines, half of the children/adolescents experienced moderate to severe pain, highlighting the need for improvement. Pain levels should be assessed both at rest and during movement. Response to treatment should be evaluated to prevent undertreatment of pain. Compliance with guidelines and professional communication are of the utmost importance for pain management in children/adolescents. Non-pharmacological methods are a valuable part of a pain management strategy. This study shows that it is important to evaluate and improve pain care also outside specialised tertiary clinics.